THE RELATIONSHIP OF KNOWLEDGE AND CHILDREN'S ATTITUDE WITH THE BEHAVIOR OF MAINTAINING HEALTHY TEETH IN MI GAYAM GAYAM DISTRICTS BOJONEGORO REGENCY - Asiyah, lsnaini; Kurniawan, Vendi Eko; Sasmito, Nanang Bagus (WELL BEING, 2016)
Tooth decay in school-aged children is a frequent problem, one of the flouncing factors is the knowledge, attitude and importance of maintaining dental health. This study aims to determine the relationship of knowledge and attitude of children with the behavior of mistiming dental health m grade V and VI students m Ml Gayam Gayam Distinct Bojonegoro Regency. This study uses correlation analytic design us mg Cross Sectional approach with population of 45 students and 45 samples. The sampling technique used 1s total sampling. The result of the research shows that most of the respondents have less knowledge than 19 respondents (42,22) and most of the students who are negative attitude are 26 respondents (57, 78%) and most of the students have less behavior as 24 respondents (53.33%). Knowledge and behavioral research vandals were analyzed by using Spean nan Rho test with 0.000 < 0,05 significance result with r value of 0.529 which means the degree of moderate closeness hence there is correlation of knowledge with behavior mistiming dental health m grade V and VI students, and attitude research van able and behavior analyzed by us mg Spearman Rho test with result of significance 0,001 < 0,05 with value r 0,483 which mean degree of moderate closeness hence there relation of attitude with behavior in maintaining dental health al student of class V and VI at Ml Gayam District Gayam Bojonegoro Regency. There is correlation between knowledge and attitude of child with dental health behavior Gayam sub district Gayam Bojonegoro district, knowledge of a child will influence attitude and behavior of child, if good knowledge hence attitude and behavior of child will be good, and vice versa. Keywords : tooth decay, knowledge, attitude, behavior of maintaining dental health, school age